2021
DOI: 10.23919/jsc.2021.0007
|View full text |Cite
|
Sign up to set email alerts
|

An Operator-Based Approach for Modeling Influence Diffusion in Complex Social Networks

Abstract: Social media have dramatically changed the mode of information dissemination. Various models and algorithms have been developed to model information diffusion and address the influence maximization problem in complex social networks. However, it appears difficult for state-of-the-art models to interpret complex and reversible real interactive networks. In this paper, we propose a novel influence diffusion model, i.e., the Operator-Based Model (OBM), by leveraging the advantages offered from the heat diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, they gave a social question-answering website knowledge dissemination network inference method. Based on the linear threshold model and value cocreation theory, the author [14] proposed a social network communication and corporate value cocreation strategy model for the characteristics of negative word-of-mouth.…”
Section: Information Dissemination Modelmentioning
confidence: 99%
“…Furthermore, they gave a social question-answering website knowledge dissemination network inference method. Based on the linear threshold model and value cocreation theory, the author [14] proposed a social network communication and corporate value cocreation strategy model for the characteristics of negative word-of-mouth.…”
Section: Information Dissemination Modelmentioning
confidence: 99%
“…However, many authors are already convinced that complex networks represent an ideal framework to investigate organized crime 1,[3][4][5][6] . In line with other research on social systems [7][8][9][10][11] , complex networks can suitably describe the intricate relations among criminals and reveal the patterns based on which criminal organizations operate. Beyond theoretical explorations, recent articles have empirically demonstrated that these methods can be useful in investigations involving drug trafficking 12 , political networks 13,14 , police intelligence networks 15 , cartel detection 16 , money laundering 17 , pedophile rings 18 , and a range of other examples [19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 67%
“…HE advancement of internet technology in recent years has promoted the rapid development of Social Internet of Things (SIoT) [1][2][3][4][5][6], which is a concept proposed through the combination of social networks [7][8][9] and Internet of Things (IoT) [10][11][12]. The attributes of social networks are introduced into the IoT to establish relationships between things-things, things-people, and people-people, so as to realize the connection, service, and application of the IoT.…”
Section: Introductionmentioning
confidence: 99%